Gold nanoparticles decorated on a graphene-periodic mesoporous silica sandwich nanocomposite as a highly efficient and recyclable heterogeneous catalyst for catalytic applications. Issue 42 (9th April 2015) - Movahed, Siyavash Kazemi; Shariatipour, Monire; Dabiri, Minoo
Abstract : Ultra-small Au nanoparticles (Au NPs) were immobilized on HS-functionalized sandwich-like periodic mesoporous silica (PMS) coated graphene (G) to form the novel nanocomposite catalyst Au NPs@HS-G-PMS. Abstract : Ultra-small Au nanoparticles (Au NPs) were immobilized on HS-functionalized sandwich-like periodic mesoporous silica (PMS) coated graphene (G) to form the novel nanocomposite catalyst Au NPs@HS-G-PMS. The synthesized Au NPs@HS-G-PMS nanocatalyst exhibited excellent catalytic activity in three kinds of organic reactions. The reduction of 4-nitrophenol by sodium borohydride, the Suzuki–Miyaura cross coupling reaction of aryl halides with phenyl boronic acid and the three component coupling reaction of aldehyde, alkyne, and secondary amine (A 3 -coupling) in water were all successfully accomplished. Most importantly, the catalyst could be used repetitively more than six times without significant deactivation.